FAKTOR RISIKO UTAMA YANG BERHUBUNGAN DENGAN KENDALI TEKANAN DARAH PADA POLISI PENDERITA HIPERTENSI LABUHAN BATU SELATAN - ELIZABETH ADINDA PUTRI HARAHAP; AHMAD HANDAYANI (JURNAL ILMIAH MAKSITEK, 2022)
Hypertension or high blood pressure is one of the diseases that contributes to the largest mortality in the world. Hypertension is characterized by high blood pressure in the systemic arteries. Blood pressure is expressed by systolic and diastolic blood pressure. According to the American Heart Association (AHA) hypertension has contributed to deaths globally around 10.4 million deaths annually and it is estimated that 1.39 billion people suffer from hypertension in 2010. There are several risk factors that cause hypertension, namely, gender, age, genetics, diet, exercise habits, obesity, alcohol consumption, excess salt consumption, smoking habits, work, stress, and comorbidities such as kidney disease and diabetes. One of the jobs that are at risk of developing hypertension is the police, where the police experience stress, the wrong diet, the wrong lifestyle. The objext of the research is To determine the main risk factors associated with the incidence of hypertension in South Labuhanbatu Police in 2021. This type of research is an analytic survey research with a cross sectional design. The sample used in the study amounted to 96 people. Data retrieval was carried out with primary data obtained by two methods, namely by conducting direct interviews by distributing questionnaires to South Labuhanbatu police personnel. Secondary data includes the number of members, member names, age of members and main duties. Then the data will be collected and analyzed. The results the research are From 96 samples, the relationship between hypertension and age was obtained p value = 0.001 and OR:0,088, Food high in salt p value = 0.018 and OR; 0,221, Family history p value = 0.715, Smoking p value = 0.932, Alcohol consumption p value = 0.902, Obesity p value = 0.379, Physical activity p value = 0.08 and OR : 3,509, Stress p value = 0.189. the conclussion if the research there is a relationship between age, physical activity, and hypertension and there is no relationship between family history or genetics, smoking, alcohol consumption, obesity, stress and hypertension. The risk factor which is the main risk factor associated with the incidence of hypertension in the South Labuhanbatu police in 2021 is physical activity